Peripheral nerve stimulation‐optimal gradient waveform design. Issue 2 (28th August 2014) - Schulte, Rolf F.; Noeske, Ralph
<x xml:space="preserve">Abstract</x> Purpose Modern magnetic resonance imaging scanners with high‐performance gradient systems have high maximum gradient strength (Gmax) and slew rate (Smax). Peripheral nerve stimulation (PNS) is often a more limiting factor for gradient waveform design than Gmax and Smax. Traditionally, the slew rate is derated globally to adhere to PNS limitations. Methods In this work, the PNS limitation is already included in the gradient waveform design in the form of a time‐varying slew rate, hence shortening the overall gradient duration. Results Spiral and echo‐planar imaging trajectories were designed with a multitude of parameters, and it was demonstrated that trajectory durations from conventional to PNS‐optimal design can be shortened by 8 and 3%, respectively. Conclusion Including PNS‐limits in the gradient waveform design can shorten the duration of gradient trajectories, thereby reducing associated artifacts. Magn Reson Med 74:518–522, 2015. © 2014 Wiley Periodicals, Inc.